COMPARING THE EFFICACY OF INTRAVENOUS ADENOSINE AND VERAPAMIL IN TERMINATION OF ACUTE PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA - Gill, Badar Ul Ahad; Bukhari, Syed Naseem Iqbal; Rashid, Munir Ahmed; Saleemi, Muhammad Sohail; Zaffar, Muhammad Zubair (Journal of Ayub Medical College Abbottabad, 2014)
Background: Paroxysmal supraventricular tachycardia (PSVT) has always been a diagnostic and therapeutic challenge for the cardiologists. There are many modalities to treat the problem. Of the available pharmacological treatment, the role of verapamil and adenosine is under debate. This study was carried out to detect and compare the efficacy of both drugs. The objective of this study was to compare the efficacy of intravenous adenosine and verapamil in termination of PSVT. Methods: This experimental study was carried out in the Emergency department of Chauhdry Pervaiz Elahi Institute of Cardiology, Multan from to August 2008 to February 2010. A total of 120 patients with PSVT were divided in two groups. Patients in group A were treated with adenosine and group B patients received verapamil. Results: The efficacy of adenosine was proven among 56 (93%) patients, while verapamil in 43 (71%) patients. The results were statistically significant (p-value <0.05). Conclusions: Although, both the drugs have high efficacy, adenosine is more effective than verapamil for termination of PSVT. Keywords: Verapamil; adenosine; Paroxysmal supraventricular tachycardia